2016 IEEE International Electron Devices Meeting (IEDM) 2016
DOI: 10.1109/iedm.2016.7838448
|View full text |Cite
|
Sign up to set email alerts
|

A CMOS-compatible large-scale monolithic integration of heterogeneous multi-sensors on flexible silicon for IoT applications

Abstract: CitationNassar JM, Sevilla GAT, Velling SJ, Cordero MD, Hussain MM (2016)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Within the same frame of reference, a recent research trend is that pursuing integration of multitudes of diverse sensors on flexible and possibly low-cost substrates. The resulting complex devices, depending on their final use, are often indicated as smart skin, and they are of great interest within the contexts of robotics and wearables [131]- [133].…”
Section: B Monolithic Orthogonally Multi-functional Devices -Watermentioning
confidence: 99%
“…Within the same frame of reference, a recent research trend is that pursuing integration of multitudes of diverse sensors on flexible and possibly low-cost substrates. The resulting complex devices, depending on their final use, are often indicated as smart skin, and they are of great interest within the contexts of robotics and wearables [131]- [133].…”
Section: B Monolithic Orthogonally Multi-functional Devices -Watermentioning
confidence: 99%
“…As sensors are an integral part of any LOC system, Nassar et al successfully showed the integration of multifunctional CMOS sensors on a large-scale flexible silicon platform. [153] Their heterogeneous and monolithic integration approach uses only CMOScompatible fabrication processes on bulk monocrystalline silicon (100). [153] The sensors include temperature RTDs, pressure, strain, and humidity, which are all vital sensing elements needed for the characterization and understanding of fluid behavior inside microfluidic channels.…”
Section: Paper Based Systemsmentioning
confidence: 99%
“…[153] Their heterogeneous and monolithic integration approach uses only CMOScompatible fabrication processes on bulk monocrystalline silicon (100). [153] The sensors include temperature RTDs, pressure, strain, and humidity, which are all vital sensing elements needed for the characterization and understanding of fluid behavior inside microfluidic channels. This flexible silicon platform is compatible with the one-chip integration of silicon-based data processing units and interface circuitry required for a complete LOC system.…”
Section: Paper Based Systemsmentioning
confidence: 99%
“…Consequently, advanced packaging has emerged, such as 2D, 2.1D, 2.3D, 2.5D, and 3D IC integration, using through-silicon via (TSV) interposer, or TSV-less, fan-out, and other interconnect technology. Numerous integration methods and fabrication techniques have been developed [1][2][3]. Furthermore, heterogeneous integration (HI) brings a new revolution for microelectronics packaging in the post-Moore era.…”
Section: Introductionmentioning
confidence: 99%